Cichlids: A Host of Opportunities for Evolutionary Parasitology - Vanhove, Maarten P M; Hablützel, Pascal I; Pariselle, Antoine; Šimková, Andrea; Huyse, Tine; Raeymaekers, Joost A M (Trends in parasitology, 2016)
Thanks to high species diversity and a broad range of speciation mechanisms, cichlid fishes represent a textbook model in evolutionary biology. They are also of substantial economic value. Despite this importance, cichlid parasites remain understudied, although some are more diverse than their hosts. They may offer important insights into cichlid evolution and the evolution of host-parasite interactions. We review five major lines of research conducted on cichlid parasites so far: the study of parasite diversity and speciation; the role of parasites in cichlid diversification; the evolutionary ecology of host specificity; historical biogeography; and biological invasions. We call for more research in these areas and suggest approaches to valorise the potential that cichlid parasites hold for the study of evolutionary parasitology.
Keywords: biologická evoluce; interakce hostitele a parazita; biogeography; cophylogeny; Animals; host specificity; cichlidy; Biological Evolution; vznik druhů (genetika); Models, Animal; adaptive radiation; invasive alien species; Host-Parasite Interactions; modely u zvířat; Genetic Speciation; zvířata; aquaculture; Biodiversity; Cichlids; výzkum; biodiverzita; Research